Accumulation and elimination of mercury in Nile Tilapia (Oreochromis niloticus) under an elevated temperature and its ambient concentrations - SUNARDI SUNARDI; ANNISA JOVIANI ASTARI; TRI DEWI KUSUMA PRIBADI; KEUKEU KANIAWATI ROSADA (Nusantara Bioscience, 2017)
Sunardi, Astari AJ, Pribadi TDK, Rosada KK. 2017. Accumulation and elimination of mercury in Nile Tilapia (Oreochromis niloticus) under an elevated temperature and its ambient concentrations. Nusantara Bioscience 9: 18-22. The problems of heavy metal pollution combined with the issue of climate warming has attracted a growing international concern, particularly to those exert very toxic effects to organisms and human, e.g. mercury. There have been evidences for temperature effect on metal uptake, accumulation and toxicity; but only few of those on metal elimination. An experimental work was set up to investigate the effect of higher water temperature and ambient concentration on both accumulation and elimination of mercury in Nile Tilapia (Oreochromis niloticus). Using 50-L aquarium, fish were exposed to room and 32oC temperature combined with 10 and 20 Î¼g/kg Hg concentration. Test fish were treated for 28 days for accumulation phase, and then transferred to Hg-free water for 7 days for elimination. Data of the Hg accumulation and elimination from the flesh, liver and kidney were analyzed using one-way Anova. The results indicated that higher water temperature and ambient mercury have increased accumulation in the liver and the kidney, but not in the flesh. Higher rate of Hg elimination occurred in higher water temperature resulting Hg deposits did not differ among treatments. However, the Hg deposits remained higher compared to those in the original state representing a potential risk to either fish or human. The kidney and the liver of Nile Tilapia seemed to be the preferable depository organs for mercury.